2016
DOI: 10.1097/sla.0000000000001164
|View full text |Cite
|
Sign up to set email alerts
|

Improving Escalation of Care

Abstract: A validated tool to assess information transfer for deteriorating surgical patients was developed and tested using simulation and real-time clinical scenarios. It may improve the quality and safety of patient care on the surgical ward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…A recent study has confirmed the effect of teaching surgeons a systematic approach in escalation of care, emphasizing that it takes more than a guideline to deliver high‐quality treatment. In the AHA study, a part of the intervention was to create focus on the vulnerable population of patients undergoing high‐risk emergency surgery and address pitfalls in treatment.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study has confirmed the effect of teaching surgeons a systematic approach in escalation of care, emphasizing that it takes more than a guideline to deliver high‐quality treatment. In the AHA study, a part of the intervention was to create focus on the vulnerable population of patients undergoing high‐risk emergency surgery and address pitfalls in treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Toolkits have also been developed in the form of checklists to capture clinical skills, team interaction skills and doctor–patient interactions during a SWR [ 56 ]. Recently, a Quality of Information Transfer Tool has been developed and validated to further improve and directly combat the communication failures within WRT members and poor escalation of care, which previous tools such as SBAR have failed to address [ 57 ]. This objective training tool incorporates key clinical information and a solid presentation structure, whilst assessing the efficacy of communication skills training during escalation of care.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the quality of referrals differed between the devices, we audio-recorded the referrals made by nurses using the pager while the data from referrals made by using Hark were automatically recorded on the app itself. We then assessed the data against a previously validated assessment tool called the QUality of Information Transfer Tool (QUIT) [ 26 ]. The QUIT is a 25-item, 7-category assessment tool comprising core components to measure the quality and content of information transfer.…”
Section: Methodsmentioning
confidence: 99%
“…Hark runs over mobile phones and tablet devices to support clinical task management. In doing so it builds on the specifications we defined to reduce adverse events associated with clinical handoff, prioritization of clinical tasks, failure to rescue, and escalation of care [ 3 , 11 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%